FSP1/S100A4-Expressing Stem/Progenitor Cells Are Essential for Temporomandibular Joint Growth and Homeostasis - Tuwatnawanit, T; Wessman, W; Belisova, D; Sumbalova Koledova, Z; Tucker, A S; Anthwal, N (Journal of dental research, 2025)
The temporomandibular joint (TMJ) is one of the most used joints in the body. Defects and wear in the cartilage of the joint, condyle, and fibrocartilage disc lie at the heart of many common TMJ disorders. During postnatal development, the condyle acts as a growth center for the mandible, with cells moving as a conveyor belt away from the top of the condyle as they differentiate. The superficial layers of the condyle have been proposed to contain stem/progenitor populations to allow growth and maintain homeostasis. Here we have focused on the role of fibroblast-specific protein 1 (FSP1; also known as S100a4) as a key fibroblast stem/progenitor marker for the condyle. Lineage tracing with FSP1-Cre;R26RmTmG mice revealed that FSP1-expressing cells were restricted to the superficial fibroblast zone, giving rise to all layers of the condyle over time. The FSP1-expressing cells overlapped with other putative stem cell markers of the condyle, such as Gli1 and scleraxis. BrdU pulse chase experiments highlighted that a subset of FSP1 fibrocartilage was label retaining, suggesting that FSP1 labels a novel stem/progenitor cell population in the condyle. Destruction of FSP1-expressing cells by conditional diphtheria toxin activity in FSP1-Cre;R26RDTA mice resulted in severe TMJ osteoarthritis with loss of the cartilage structure. Lgr5-expressing cells in the superficial layer of the condyle have been shown to create a Wnt inhibitory niche. FSP1 expression postnatally was associated with a reduction in canonical Wnt activity in the condyle. Importantly, constitutive activation of Wnt/β catenin in FSP1-expressing cells led to a downregulation of FSP1 and progressive postnatal loss of TMJ condylar hyaline cartilage due to loss of the superficial stem/progenitor cells. These data demonstrate a novel role for FSP1-expressing cells in the superficial zone in growth and maintenance of the TMJ condylar cartilage and highlight the importance of regulating Wnt activity in this population.
Keywords: fibrocartilage; Receptors, G-Protein-Coupled; Temporomandibular Joint; Mice, Transgenic; Wnt signaling; myši transgenní; Mandibular Condyle; condyle; zvířata; myši; temporomandibulární kloub; Mice; S100 Calcium-Binding Protein A4; osteoarthritis; temporomandibular disorders; Stem Cells; S100 kalcium vázající protein A4; homeostáza; processus condylaris mandibulae; Homeostasis; stem cell; fibroblasty; kmenové buňky; Animals; receptory spřažené s G-proteiny; Fibroblasts